An Exploratory Study Toward the Preferred Conversational Style for Compatible Virtual Agents - Shamekhi, Ameneh; Czerwinski, Mary; Mark, Gloria; Novotny, Margeigh; Bennett, Gregory (Intelligent Virtual Agents, 2017)
Designing virtual personal assistants that are able to engage users in an interaction have been a challenge for HCI researchers for the past 20 years. In this work we investigated how a set of vocal characteristics known as “conversational style” could play role in engaging users in an interaction with a virtual agent. We also examined whether the similarity attraction principle influences how people orient towards agents with different styles. Results of a within subject experiment on 102 subjects revealed that users exhibited similarity attraction toward computer agents, and preferred the agent whose conversational style matched their own. The study results contribute to our understanding of how the design of intelligent agents’ conversational style influences users’ engagement and perceptions of the agent, compared to known human-to-human interaction.